Defining the socio-economic and environmental determinants for high tobacco consumption behaviors among interstate migrant construction workers in Chennai: an observational analysis - Sucharitha, Sree T.; Arumugam, Balaji; E., Suganya; S., Divyadharshini; P., Akshaya (International Journal Of Community Medicine And Public Health, 2020)
Background: Global Adult Tobacco Survey-2 (GATS) reveals significant improvements in the decline of tobacco consumption in the past decades, however vulnerable population groups such as migrant construction workers tobacco consumption behaviors in Chennai remain understudied, thus the study was planned to estimate the socio-economic and environmental determinants for high tobacco consumption behaviors among interstate migrant construction workers in Chennai. Methods: A cross sectional survey was undertaken using a pre-tested structured questionnaire adapted from GATS survey questionnaire assessing the socio-demographic and environmental determinants for tobacco use among study population across 13 construction sites in Chennai during May-September 2019. Data was entered in MS-Excel and analysed using SPSS. Results: Among 345 migrant construction workers, mean age of the subjects was 28.42±8.7 years, 338 (98%) were current tobacco users by smoking, chewing, snuffing, of whom 198 (58.6%) used smokeless forms of tobacco like gutkha, khaini, chewing tobacco leaves, betel quid, tobacco snuff, 98 (29%) were smokers and 42 (12.4%) were dual users i.e. both cigarettes and beedis. Khaini (57%) is the dominant form of tobacco used among migrant construction workers. Mean age of initiation of tobacco use was 21.58 years and 21.17, and 22.73 and 19.5 years for smoking, SLT and dual users respectively. The migrant construction workers with no formal literacy(p=0.000), monthly income of more than 10000 (p=0.020) Indian rupees and migrants for less than one year duration (p=0.05)were more likely using the smokeless tobacco than any other socio demographic group. Conclusions: Tobacco prevalence especially smokeless tobacco use is alarmingly high among interstate migrant construction workers to Chennai.